CIIA prevents SOD1(G93A)-induced cytotoxicity by blocking ASK1-mediated signaling - Lee, Jae Keun; Hwang, Sang Gil; Shin, Jin Hee; Shim, Jaekyung; Choi, Eui-Ju (Frontiers in Cellular Neuroscience, 2014)
Amyotrophic lateral sclerosis (ALS) is an adult-onset neurodegenerative disease with higher selectivity in degeneration of motor neurons. However, the molecular mechanism by which the ALS-linked mutants of human superoxide dismutase 1 (SOD1) gene induce neurotoxicity remains obscure yet. Here, we show that depletion of CIIA expression by RNA interference (RNAi) promoted cytotoxicity caused by ALS-linked G93A mutant of the SOD1 gene. The RNAi-mediated knockdown of CIIA also enhanced the SOD1(G93A)-induced interaction between ASK1 and TRAF2 as well as ASK1 activity. Furthermore, endogenous silencing of CIIA by RNAi augmented the effects of SOD1(G93A) on reduction of mitochondria membrane potential (Δψm), release of cytochrome c into the cytoplasm, and caspase activation. Together, our results suggest that CIIA negatively modulates ASK1-mediated cytotoxic signaling processes in a SOD1(G93A)-expressing cellular model of ALS.